2018
DOI: 10.1007/s00062-018-0697-x
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Stenting after Failure of Thrombectomy with the emboTrap® Device

Abstract: Intracranial stenting after failure of recanalization with thrombectomy led to a better rate of clinical outcome than leaving the patient non-recanalized. The required antiplatelet therapy, predominantly abciximab, did not lead to additional ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…However, a post hoc subanalysis showed that there were no outcome differences in SAMMPRIS patients comparing early and late therapy initiation after the qualifying event 20. The question of the best timing for endovascular therapy is still a matter of current debate since the latest results on stenting for acute stroke patients with tandem occlusions or after failed thrombectomy showed no increased risk of ICH, in some cases even combined with IVT 7 21–23. Thus antithrombotic therapy management might be more important than timing.…”
Section: Discussionmentioning
confidence: 99%
“…However, a post hoc subanalysis showed that there were no outcome differences in SAMMPRIS patients comparing early and late therapy initiation after the qualifying event 20. The question of the best timing for endovascular therapy is still a matter of current debate since the latest results on stenting for acute stroke patients with tandem occlusions or after failed thrombectomy showed no increased risk of ICH, in some cases even combined with IVT 7 21–23. Thus antithrombotic therapy management might be more important than timing.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, evaluating the efficacy and safety of rescue stenting (RS) in patients with proximal vessel occlusion in the anterior circulation has attracted much interest. Previous studies indicate that RS is significantly associated with successful reperfusion and good outcomes without increasing the risk of symptomatic intracranial hemorrhage (sICH) or mortality 10–13. Nevertheless, further investigation is needed to confirm any conclusions reached on this subject because of the relatively small numbers of patients who have been treated with RS.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the retrospective and anonymized study design, informed consent of the patients was not required. Some data were part of previously published cohorts (7,11).…”
Section: Patient Selectionmentioning
confidence: 99%
“…Accordingly, the best currently available evidence for the endovascular treatment of ICAD is based on the SAMMPRIS and the VISSIT study (4,5) showing the superiority of best medical treatment over elective intracranial stenting. Recently, acute intracranial stenting (ICS) has been reported to be a highly promising bailout strategy for theses frustrating thrombectomy cases with predictably poor outcomes (6)(7)(8)(9)(10)(11). Since these cases are still rare, past retrospective studies mostly analyzed heterogeneous cohorts, including a wide range of stroke severities (12).…”
Section: Introductionmentioning
confidence: 99%